The Influence of Aerobic and Ergonomic Combination Gymnastics in Blood Pressure in Adult Age Patients - Fadli Maulana Agitiyo; Abu Bakar; Laily Hidayati (Critical Medical and Surgical Nursing Journal (CMSNJ), 2022)
Introduction: Hypertension is a disease characterized by increased blood pressure in the body. One of the non-pharmacological management of hypertension is to do a combination of aerobic and ergonomic exercises to optimize the heart and blood vessels. This study describes the effect of a combination of aerobic and ergonomic gymnastics on blood pressure in adult sufferers in Kepuh Village, Palimanan District, Cirebon. Methods: The research design used in this study was a pre-experimental design with a pretest–posttest one-group design and using a probability sampling technique with a purposive sampling type of 25 respondents which included patients aged 25-45 years who suffered from hypertension. This study used observation sheets and blood pressure measurements using a sphygmomanometer, and data analysis using the Wilcoxon test with a significance value of 5% (0.05).  Results: Research results in the Wilcoxon test for the pre and post-systolic blood pressure showed a value of p = 0.000, while for pre and post-diastolic blood pressure the value was p = 0.001 which indicates that there is an effect of combined aerobic and ergonomic exercise on blood pressure in adult patients in Kepuh Village, Palimanan District, Cirebon Regency. Conclusion: The combination of aerobic and ergonomic exercise has an effect on systolic and diastolic blood pressure in adult hypertensive patients in Kepuh Village, Cirebon. Therefore, a combination of aerobic and ergonomic exercise can be an alternative to regulating blood pressure in adult hypertensive patients.